2014
DOI: 10.1039/c4ra02238f
|View full text |Cite
|
Sign up to set email alerts
|

N-Methylbenzoaza-18-crown-6-ether derivatives as efficient alkali metal cations sensors: the dipole moment and first hyperpolarizability

Abstract: 1-Li+, 1-Na+ and 1-K+ complexes formed by N-methylbenzoaza-18-crown-6-ether derivatives with one alkali metal cation were investigated. Their dipole moments and first hyperpolarizabilities take on opposite trends with increasing the atomic number.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Therefore, we have calculated the nonlinear optical properties of compounds 1, 2 and 3 by using three methods (BHandHLYP, CAM-B3LYP and M06-2X). 31 The data obtained by three methods are very similar, indicating that the calculated results are reliable. On the other hand, it has been proposed by Champagne and Nakano, for a medium-size system, the BHandHLYP method can reproduce the (hyper)polarizability values from more sophisticated coupled cluster.…”
Section: Computational Detailssupporting
confidence: 61%
See 1 more Smart Citation
“…Therefore, we have calculated the nonlinear optical properties of compounds 1, 2 and 3 by using three methods (BHandHLYP, CAM-B3LYP and M06-2X). 31 The data obtained by three methods are very similar, indicating that the calculated results are reliable. On the other hand, it has been proposed by Champagne and Nakano, for a medium-size system, the BHandHLYP method can reproduce the (hyper)polarizability values from more sophisticated coupled cluster.…”
Section: Computational Detailssupporting
confidence: 61%
“…29 On the other hand, numerous valuable papers have demonstrated that the alkali doping can signicantly enhance the NLO response of studied systems. [30][31][32][33][34][35][36][37] Inspired by our previous papers and the advantages of crown compounds (the structural exibility and the interaction with alkali metal cations), we intend to investigate the effect of the ring sizes and the nature of alkali metal cations on the NLO properties. Firstly, based on the synthesized compound 2, the compounds 1 and 3 are designed.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the latter method can be chosen especially for larger systems as the CCSD(T) method is computationally very costly and quite difficult to perform. The BHHLYP 68,69 and wB97XD 70 functionals are also used widely in evaluating the first hyperpolarizability for alkali and alkaline earth metal doped organometallic systems. Thus, for the investigated molecular complexes, the chosen DFT functionals BHHLYP, CAM-B3LYP and wB97XD can provide satisfactory results of first hyperpolarizability.…”
Section: Methodsmentioning
confidence: 99%
“…Their cation selectivity is dependent on the size and charge density of the ion and the crown ether cavity and is mainly achieved by ion-dipole interactions [21]. Among them, 15-crown-5 and 18-crown-6 are good hosts for sodium and potassium ions, respectively, and have been investigated for the development of selective fluorescent, potentiometric and electrochemical sensors for the detection of these biologically important electrolytes in solution [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%